2023
DOI: 10.1128/msphere.00602-22
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochemical and Seasonally Conditioned Changes of Microbial Communities in the Tufa-Forming Freshwater Network Ecosystem

Abstract: Plitvice Lakes represent a rare freshwater ecosystem consisting of a complex network of lakes and waterfalls connecting them, as well as rivers and streams supplying water to the lake basin. The unique geomorphological, hydrological, biogeochemical, and biological phenomenon of Plitvice Lakes lies in the biodynamic process of forming tufa barriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Bishav et al observed that such variations in the Great Salt Lake's northern and southern regions resulted in distinct species diversity [13]. The diverse microbial communities in the Plitvice lakes were linked to unique network ecosystems formed by varying salinity across different landforms [14]. This suggests that salinity differences within the same region may create a unique barrier affecting microbial diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Bishav et al observed that such variations in the Great Salt Lake's northern and southern regions resulted in distinct species diversity [13]. The diverse microbial communities in the Plitvice lakes were linked to unique network ecosystems formed by varying salinity across different landforms [14]. This suggests that salinity differences within the same region may create a unique barrier affecting microbial diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Bishav et al found that the difference in salinity between the northern and southern regions of the hypersaline Great Salt Lake led to species diversity (14). Plitvice lakes with rich microbial communities were attributed to rare network ecosystems of varying salinity composed of several different landforms (15). Perhaps the difference in microbial diversity due to different salinities in the same area is a unique barrier system.…”
Section: Introductionmentioning
confidence: 99%